Time-varying benefits of cross-asset and cross-region portfolio diversification - Gorny, Moritz Fabio (2017)
The thesis uses return data on equities, bonds, commodities and real estate for the U.S., Europe, Asia and Latin America to examine diversification potentials. The analysis focuses on benefits of cross-asset and cross-region diversification as well as the impact of financial distress on those strategies and portfolio performances. It concludes that diversification benefits vary over time and decrease in bear markets due to higher correlation. Investmentgrade bonds and gold have shown the highest diversification benefits for equity investors during financial distress. Assets from emerging markets seem to be less sensitive to global market drops and show more constant performances.